Peran Literasi Sains dalam Meningkatkan Kompetensi Siswa SMK: Sebuah Tinjauan Literatur - Miftahul Hasanatun Alfiah; Bramastia Bramastia; Sukarmin Sukarmin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This study examines the role of science literacy in enhancing the competencies of Vocational High School (SMK)students through a systematic literature review. Science literacy, encompassing the understanding of scientificconcepts and their practical application, is crucial for preparing SMK students to meet the demands of a technology-driven and innovative industry. The research finds that science literacy not only improves technical skills andproblem-solving abilities but also contributes to the development of soft skills, such as critical thinking andcommunication. The implications of enhancing science literacy for curriculum development and teaching methodsin SMK highlight the need for integrating science with vocational skills, adopting project-based learningapproaches, and utilizing digital technology to enrich the learning experience. The findings are expected to provideinsights for educators and policymakers in developing effective strategies to strengthen science literacy in vocationaleducation.